Physical growth and changes in intermittent endurance run performance in young male Basque soccer players - Carvalho, H.-M.; Bidaurrazaga-Letona, I.; Lekue, J. A.; Amado, M.; Figueiredo, A. J.; Gil, S. M. (Research in Sports Medicine, 2014)
The present 4-year longitudinal study examined physical growth and development of intermittent endurance run performance in young Basque soccer players aged 10-15 years applying multilevel regression modeling. Anthropometry, predicted adult stature and Yo-Yo Intermittent Recovery level 1 test (Yo-Yo IR1) of players from the under-11 teams from the Athletic Club of Bilbao were measured at pre- and end-season (two measurements per year of study, n = 33 considered for analysis). A non-linear effect of age on intermittent endurance run was observed, with significantly higher increases in Yo-Yo IR1 between 10-11 year-old and 14-15 year-old players. The development of Yo-Yo IR1 performance in all the years of the study was influenced positively by training exposure during the seasons (P < 0.01) and independent of maturity status and body size (P > 0.05). The steady development of intermittent endurance run performance during pubertal years in adolescent Basque soccer players is partially influenced by training exposure.